Design and develop current limiter for mosfet during overvoltage operation - Nur Haezah, Mamat (2012)
Gate drive circuit is important for the purpose of controlling signal to the gate of power switch. Currently, most gate drive circuit is designed without current control; as such the overload, short circuit or overvoltage will cause permanent damage to the power switch. Protecting the power switch from being damage from the overload, short circuit and overvoltage must be considered seriously. In this project, the new design of gate drive circuit with current limiter to controls the gate voltage signal to the MOSFET and limits the current flow through the Metal-Oxide Semiconductor Field-Effect Transistor (MOSFET) during overvoltage. It will use the current limiter circuit to control voltage supplied to the gate of power switch and thus limit the amount of current flow to the MOSFET during overvoltage operation. Hence the gate drive circuit with current limiter is very important to protect the power switch from over current.